Understanding the growth of micro and nano-crystalline AlN by thermal plasma process - Kanhe, Nilesh S.; Nawale, Ashok B.; Gawade, Rupesh L.; Puranik, Vedavati G.; Bhoraskar, S. V.; Das, Asoka K.; Mathe, Vikas L. (Journal of Crystal Growth, 2012)
We report the studies related to the growth of crystalline AlN in a DC thermal plasma reactor, operated by a transferred arc plasma torch. The reactor is capable of producing the nanoparticles of Al and AlN depending on the composition of the reacting gas. Al and AlN micro crystals are formed at the anode placed on the graphite and nano crystalline Al and AlN gets deposited on the inner surface of the plasma reactor. X-ray diffraction, Raman spectroscopy analysis, single crystal X-ray diffraction and TGA-DTA techniques are used to infer the purity of post process crystals as a hexagonal AlN. The average particle size using SEM was found to be around 30 mu m. The morphology of nanoparticles of Al and AlN, nucleated by gas phase condensation in a homogeneous medium were studied by transmission electron microscopy analysis. The particle ranged in size between 15 and 80 nm in diameter. The possible growth mechanism of crystalline AlN at the anode has been explained on the basis of non-equilibrium processes in the core of the plasma and steep temperature gradient near its periphery. The gas phase species of AlN and various constituent were computed using Murphy code based on minimization of free energy. The process provides 50% yield of microcrystalline AlN and remaining of Al at anode and that of nanocrystalline h-AlN and c-Al collected from the walls of the chamber is about 33% and 67%, respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from high temperature solutions; Nitride; Semiconducting aluminum compound